Outcome of giant pituitary tumors requiring surgery - Gaillard, Stephan; Adeniran, Sosthène; Villa, Chiara; Jouinot, Anne; Raffin-Sanson, Marie-Laure; Feuvret, Loic; Verrelle, Pierre; Bonnet, Fidéline; Dohan, Anthony; Bertherat, Jérôme; Assié, Guillaume; Baussart, Bertrand (Frontiers in Endocrinology, 2022)
Objective: The management of giant pituitary tumors is complex, with few publications and recommendations. Consequently, patient’s care mainly relies on clinical experience. We report here a first large series of patients with giant pituitary tumors managed by a multidisciplinary expert team, focusing on treatments and outcome. Methods: A retrospective cohort study was conducted. Giant pituitary tumors were defined by a main diameter > 40mm. Macroprolactinomas sensitive to dopamine agonists were excluded. All patients were operated by a single neurosurgical team. After surgery, multimodal management was proposed, including hormone replacement, radiotherapy and anti-tumor medical therapies. Outcome was modeled using Kaplan-Meyer representation. A logistic regression model was built to identify the risk factors associated with surgical complications. Results: 63 consecutive patients presented a giant adenoma, most often with visual defects. Patients were operated once, twice or three times in 59%, 40% and 1% of cases respectively, mainly through endoscopic endonasal approach. Giant adenomas included gonadotroph, corticotroph, somatotroph, lactotroph and mixed GH-PRL subtypes in 67%, 14%, 11%, 6% and 2% of patients respectively. Vision improved in 89% of patients with prior visual defects. Severe surgical complications occurred in 11% of patients, mainly for tumors > 50 mm requiring microscopic transcranial approach. Additional radiotherapy was needed for 29% of patients, 3 to 56 months after first surgery. For 6% of patients, Temozolomide treatment was required, 19 to 66 months after first surgery. Conclusions: Giant pituitary tumors require multimodal management, with a central role of surgery. Most often, tumor control can be achieved by expert multidisciplinary teams.